Enhancing surface wear resistance of aluminum and magnesium alloys through friction stir processed surface composites: a critical review - Hemendra Patle; Ratna Sunil Buradagunta; Ravikumar Dumpala (Industrial Lubrication and Tribology, 2025)
Purpose The purpose of present review is to provide a critical summary on producing surface composites of Al and Mg composites by friction stir processing (FSP). More focus is given on surface hardness and wear properties of the composites produced by FSP. Design/methodology/approach The approach to present the review on developing surface composites by friction stir processing (FSP) includes a detailed introduction to FSP and the role of process parameters on successfully producing the Al and Mg based composites followed by presenting surface hardness and wear characteristics of these composites. Findings The reported literature summary concludes using FSP as surface engineering method to enhance wear resistance of Al and Mg components as a promising strategy. Originality/value The presented review helps the researchers to refer a critical summary on developing surface composites of Al and Mg by FSP specifically to attain a comprehensive understanding of wear properties of these surface composites. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-04-2025-0194/